Tofacitinib Ameliorates Murine Lupus and Its Associated Vascular Dysfunction. Issue 1 (January 2017) - Furumoto, Yasuko; Smith, Carolyne K.; Blanco, Luz; Zhao, Wenpu; Brooks, Stephen R.; Thacker, Seth G.; Zarzour, Abdalrahman; Sciumè, Giuseppe; Tsai, Wanxia L.; Trier, Anna M.; Nunez, Leti; Mast, Laurel; et al.
Abstract : Objective: Dysregulation of innate and adaptive immune responses contributes to the pathogenesis of systemic lupus erythematosus (SLE) and its associated premature vascular damage. No drug to date targets both systemic inflammatory disease and the cardiovascular complications of SLE. Tofacitinib is a JAK inhibitor that blocks signaling downstream of multiple cytokines implicated in lupus pathogenesis. While clinical trials have shown that tofacitinib exhibits significant clinical efficacy in various autoimmune diseases, its role in SLE and the associated vascular pathology remains to be characterized. Methods: MRL/ lpr lupus‐prone mice were administered tofacitinib or vehicle by gavage for 6 weeks (therapeutic arm) or 8 weeks (preventive arm). Nephritis, skin inflammation, serum levels of autoantibodies and cytokines, mononuclear cell phenotype and gene expression, neutrophil extracellular traps (NETs) release, endothelium‐dependent vasorelaxation, and endothelial differentiation were compared in treated and untreated mice. Results: Treatment with tofacitinib led to significant improvement in measures of disease activity, including nephritis, skin inflammation, and autoantibody production. In addition, tofacitinib treatment reduced serum levels of proinflammatory cytokines and interferon responses in splenocytes and kidney tissue. Tofacitinib also modulated the formation of NETs and significantly increased endothelium‐dependent vasorelaxation and endothelial differentiation. The drug was effective in both preventive and therapeutic strategies. Conclusion: Tofacitinib modulates the innate and adaptive immune responses, ameliorates murine lupus, and improves vascular function. These results indicate that JAK inhibitors have the potential to be beneficial in SLE and its associated vascular damage.